Pengaruh Variasi Kemiringan Sudut Kontak Primary Pulley DanVariasi Massa Roller Terhadap Kinerja Motor Bakar Matic Injeksi 110 Cc - Noviana Sari; Ryo Armando Pratama; M.Abiyyu Raafi; Lihananda Septianur Falah; Trisma Jaya Saputra (Pusat Riset dan Inovasi Nasional, 2023)
Based on observations from motorcycle drivers with automatic transmissions, there are several commonly criticized complaints about the lack of responsiveness. There are many ways to improve motorcycle performance. One of them is to change the contact angle inclination of the primary he pulley of the continuously variable transmission (CVT) and change the mass of the pulley accordingly. The method used in this study is an experimental research method. This method works by directly testing the effect of one variable on another. The purpose of this study is to investigate the effect of varying primary pulley tilt on power, torque, slip ratio and fuel consumption of a 110cc bike when the primary pulley contact angle and roller mass tilt are varied. That's it. The primary pulleys have contact angles of 13.5° and 14°, and pulley masses of 13 and 15 grams. The subject of this study is a Honda Beat PGM-FI 110cc bike with an engine speed of 2000-4000 rpm. 500rpm According to the results of the studies conducted, a 13.5° primary roll and a 13 gram roll achieved the best results in all tests. Maximum torque is 24.95Nm at 2000rpm and maximum power is 8.0hp at 2500rpm.